Physical condition and heart rate rest of yogyakarta rugby pon team players during the COVID-19 pandemic - Antonius Tri Wibowo (H.S. Skovoroda Kharkiv National Pedagogical University, 2020)
Aim: To identify the correlation between different fitness indicators of rugby players in training conditions during quarantine related to Covid-19. Material and methods. The study involved athletes from PON Rugby DIY (n = 28, including 15 male athletes and 13 female athletes). To assess the level of physical fitness, the following tests were used: to assess the level of strength, push ups for 1 minute (number) and squats for one minute (number) were used; the yo-yo test was used to assess the level of endurance; speed was assessed using a 40 meter running test (s); agility by performing an Illinois agility test; power (speed-strength abilities) was assessed by the value of the vertical jump (cm); and for the heart rate was determined by the athlete independently within 60 seconds after waking up. The data collection method in this study is test and questionnaire. Data analysis was performed using Pearson correlation analysis using SPSS V 25 software. Results. It was shown that endurance has a strong correlation with power with r value (0.651) and significant p = 0.000. Speed ??also has a strong correlation with strength, as evidenced by the r (0.538) value with a significant p = 0.003. Strength has a strong correlation with power, as evidenced by the value of r (0.561) with a significant value of p = 0.002. Speed ??has a very strong correlation with agility, as evidenced by the value (0.935) with a significant p = 0.000. Conclusions. It was found that endurance does not correlate with resting heart rate, and endurance does not correlate with strength, because the load of the training program was not optimally implemented by athletes in the Covid-19 quarantine.